Structural insights into 3Fe–4S ferredoxins diversity in M. tuberculosis highlighted by a first redox complex with P450 - Gilep, Andrei; Varaksa, Tatsiana; Bukhdruker, Sergey; Kavaleuski, Anton; Ryzhykau, Yury; Smolskaya, Sviatlana; Sushko, Tatsiana; Tsumoto, Kouhei; Grabovec, Irina; Kapranov, Ivan; Okhrimenko, Ivan; Marin, Egor; et al. (Frontiers in Molecular Biosciences, 2023)
Ferredoxins are small iron–sulfur proteins and key players in essential metabolic pathways. Among all types, 3Fe–4S ferredoxins are less studied mostly due to anaerobic requirements. Their complexes with cytochrome P450 redox partners have not been structurally characterized. In the present work, we solved the structures of both 3Fe–4S ferredoxins from M. tuberculosis—Fdx alone and the fusion FdxE–CYP143. Our SPR analysis demonstrated a high-affinity binding of FdxE to CYP143. According to SAXS data, the same complex is present in solution. The structure reveals extended multipoint interactions and the shape/charge complementarity of redox partners. Furthermore, FdxE binding induced conformational changes in CYP143 as evident from the solved CYP143 structure alone. The comparison of FdxE–CYP143 and modeled Fdx–CYP51 complexes further revealed the specificity of ferredoxins. Our results illuminate the diversity of electron transfer complexes for the production of different secondary metabolites.